2015
DOI: 10.1007/s10803-015-2623-2
|View full text |Cite
|
Sign up to set email alerts
|

Is Social Categorization the Missing Link Between Weak Central Coherence and Mental State Inference Abilities in Autism? Preliminary Evidence from a General Population Sample

Abstract: We explore the relationship between the 'theory of mind' (ToM) and 'central coherence' difficulties of autism. We introduce covariation between hierarchically-embedded categories and social information--at the local level, the global level, or at both levels simultaneously--within a category confusion task. We then ask participants to infer the mental state of novel category members, and measure participants' autism-spectrum quotient (AQ). Results reveal a positive relationship between AQ and the degree of loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 79 publications
4
48
1
Order By: Relevance
“…This study therefore offers a unique view and test of social identity processes, demonstrating that the assumptions of the social identity approach can be usefully applied to autistic people as a social and psychological group. However, other research has demonstrated that some of the cognitive and social abilities needed to self-identify and create social cohesion are impaired in this group (e.g., Berna et al, 2016;Skorich et al, 2016). The current results do not explain how social identity processes prevail in autistic people despite significant barriers in terms of social cognitive abilities.…”
Section: Strengths Limitations and Future Directionscontrasting
confidence: 91%
See 1 more Smart Citation
“…This study therefore offers a unique view and test of social identity processes, demonstrating that the assumptions of the social identity approach can be usefully applied to autistic people as a social and psychological group. However, other research has demonstrated that some of the cognitive and social abilities needed to self-identify and create social cohesion are impaired in this group (e.g., Berna et al, 2016;Skorich et al, 2016). The current results do not explain how social identity processes prevail in autistic people despite significant barriers in terms of social cognitive abilities.…”
Section: Strengths Limitations and Future Directionscontrasting
confidence: 91%
“…For example, social and self‐categorization skills are key to identifying members of an in‐group prior to forming affiliations with the group. A recent study conducted by Skorich et al () found that people with autism spectrum traits are more likely to process social information at a localized rather than a global level, and that this affects mental state inference skills. This evidence suggests that the more localized social categorization found in autistic people contributes to their deficits in understanding others' thinking.…”
Section: Social Identity Processes In Autistic Peoplementioning
confidence: 99%
“…There are features of autism which may contribute to this greater rate of gender diversity and lower gender identification across the sexes, however there is limited research available about how autistic individuals think about gender as a concept as compared to typically developing individuals, and so the following theories may or may not relate to gender identity in this group. Deficits in self-categorisation may pose challenges to autistic individuals in identifying with a gender label (Skorich et al 2016 ), as individuals who struggle to place themselves in social categories may develop more idiosyncratic gender identities compared to typically developing people who are more readily able to categorise themselves within a gender group. Deficits in social communication may result in less knowledge and understanding of gender norms, or a freedom from gender norms allowing for more diverse gender expression, and a lower level of social reciprocity and affiliation with members of a gender group.…”
Section: Discussionmentioning
confidence: 99%
“…An association between Weak Central Coherence and Theory of Mind is also posited by Skorich and colleagues [6,58,59] who suggest that Weak Central Coherence affects the cogni-tive process of self-categorization, which in turn disrupts the shared attention mechanism, one of the components of the theory of mind system. Their evidence for this is an association among neurotypical participants between scores on the autism-spectrum quotient and theory of mind performance, mediated by a social categorization task.…”
Section: Weak Central Coherence and Social Perceptionmentioning
confidence: 75%
“…Fundamental to the current study is the question of whether central coherence is related to [19,58,59], or independent of [23], social perception in autism. By measuring the relationship between social and non-social measures of global precedence, we can test whether social perceptual anomalies in autism are related to central coherence.…”
Section: Weak Central Coherence and Social Perceptionmentioning
confidence: 99%